1985
DOI: 10.1128/jcm.22.4.501-504.1985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mannitol salt agar with oxacillin as a screening medium for methicillin-resistant Staphylococcus aureus

Abstract: We evaluated the use of mannitol salt agar with oxacillin for use as a primary screening medium for the simultaneous detection and identification of methicillin-resistant Staphylococcus aureus in clinical surveillance specimens. Oxacillin agar dilution susceptibility tests with mannitol salt agar and Mueller-Hinton agar were performed in parallel with disk-agar diffusion testing on 95 oxacillin-susceptible and 105 oxacillin-resistant S. aureus stock isolates. MICs were found to be comparable, showing distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 10 publications
3
15
0
Order By: Relevance
“…In this report we propose that the action of lipase activity on egg yolk and the addition of 7.5% sodium chloride to the phenol red-mannitol-agar results in an improved medium for the recognition of coagulase-positive staphylococci, while it inhibits most gram-negative bacteria. Our findings were very similar to those obtained in other studies (7,9,16) and showed that LSM agar allows for the good growth of all staphylococcal species, while it inhibits most gram-negative rods. The medium turns yellow for mannitol-positive organisms and gives an opaque (precipitated) zone around colonies that are lipovitellenin positive.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this report we propose that the action of lipase activity on egg yolk and the addition of 7.5% sodium chloride to the phenol red-mannitol-agar results in an improved medium for the recognition of coagulase-positive staphylococci, while it inhibits most gram-negative bacteria. Our findings were very similar to those obtained in other studies (7,9,16) and showed that LSM agar allows for the good growth of all staphylococcal species, while it inhibits most gram-negative rods. The medium turns yellow for mannitol-positive organisms and gives an opaque (precipitated) zone around colonies that are lipovitellenin positive.…”
Section: Resultssupporting
confidence: 92%
“…A recent study (14) of 53 microbiology laboratories affiliated with university or tertiary care hospitals in 10 European countries reported an MRSA screening program with divided agar plates, half of which consisted of MSA and the other half of which consisted of Mueller-Hinton agar supplemented with 4% NaCl and 6 mg of oxacillin per liter. Results from our replicator studies and other studies (9,16) reinforce the fact that although fermentation of mannitol has been described as a characteristic for the differentiation of coagulase-positive and coagulase-negative staphylococci, the use of MSA plates requires secondary confirmation testing with colonies from the primary plates. LSM agar may also have an added advantage over Mueller-Hinton agar supplemented with 4% NaCl and oxacillin, since studies by Zonby and Starzyk (16) pointed out that the MRSA screen plate medium does not inhibit some gram-negative bacilli such as Proteus spp.…”
Section: Resultssupporting
confidence: 80%
“…Initially, nuc-positive broth samples were assayed for the presence of mecA genes, but this had limited value (results not shown), probably because of a high frequency of mecA genes in coagulase-negative staphylococci present in the samples. Many different solid culture media [17,21,22] and enrichment broth media [12,[23][24][25][26] have been described for the cultivation of S. aureus. Some media include NaCl at high concentrations to favour growth of staphylococci, although some clones have a documented lower salt-tolerance [27], as well as oxacillin or methicillin to make them selective for MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol-salt agar and related media (2,4,8) are widely used for specific screening of S. aureus in potentially contaminated samples. They can be supplemented with antibiotics in order to detect methicillin-resistant S. aureus (MRSA) isolates (13,18). However, the average sensitivity and specificity of mannitol-salt agar (10,12,15) do not qualify it for use for early isolation and presumptive identification of S. aureus in all clinical specimens, although supplementation with egg yolk was shown to be of clinical interest (15).…”
mentioning
confidence: 99%